Antimicrobial of Ethanolic Extract from Marpuyan Stem Bark (Rhodamnia cinerea Jack) - Nasution, Musyirna Rahmah; Cahyani, Ardhia Regita; Aqilla, Alya; Fitri, Valentina; Triani, Leni (Acta Chimica Asiana, 2024)
The Bark of Marpuyan Tree (Rhodamnia cinerea Jack) is a plant that has been empirically used by communities in Indonesia for the treatment of infectious diseases caused by bacteria and fungi. The bark of Marpuyan contains flavonoids, phenolics, and saponins. This study aimed to evaluate the antibacterial and antifungal activities of the ethanol extract of the bark of Marpuyan using the disc diffusion method at various extract concentrations, namely 30%, 25%, 15%, 10%, and 5%. The results of the antibacterial activity test against Gram-positive bacteria (Staphylococcus aureus, Staphylococcus epidermidis, and Bacillus subtilis) showed inhibitory zones with respective diameters of 11.67±0.21 mm, 12.29±0.43 mm, and 12.78±0.14 mm. These results indicate weak antibacterial activity. In the antibacterial activity test against Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa, and Salmonella typhi), inhibitory zones were found with respective diameters of 13.05±0.05 mm, 12.58±1.78 mm, and 10.98±0.21 mm. These results also indicate weak antibacterial activity. However, in the antifungal activity test, no activity was found against Candida albicans and Malassezia furfur. Nevertheless, the ethanol extract of Marpuyan bark showed moderate antifungal activity against Trichophyton mentagrophytes, with an inhibitory zone diameter of 15.44±2.02 mm.